Stroke characteristics of elite swimmers during a sprint interval training set - Barden, J.; Kell, R. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Understanding the relationships between swimming velocity (V), stroke rate (SR) and stroke length (SL) can provide important information about the training status and technical development of competitive swimmers (1,2,4). Most stroke parameter relationship (i.e., V, SR and SL) studies have taken place during major competitions which permit rare opportunities to study the technique of the world`s best swimmers (1,3). Surprisingly, few studies have been conducted during training, either across several training sessions or during a controlled interval training set (4). The purpose of this study was to investigate V, SR and SL relationships during a sprint interval training set that progressively increased in intensity. Eleven (3 male, 8 female) elite national-calibre swimmers performed a series of 8 x 100m swims in a 25m pool. The swimmers were paced so that the first 100m swim was equal to 65% of their best time. The target time for each subsequent 100m repeat decreased by 5%, so that the last 100m swim was equal to the swimmer`s best time (a maximal effort). Rest intervals were individualized according to a 1:2 work/rest ratio. Each subject completed the set using his/her best stroke, with 5 subjects swimming freestyle, 3 backstroke, 2 butterfly and 1 breaststroke. A 5m recording zone (mid-pool, 10m on either side) was used to measure V and SR for each 25m length. Stroke parameter data were compared between and within subjects using Pearson correlation and repeated measures ANOVA. For all subjects and strokes, V was highly correlated with SR (r = 0.90 ± 0.07), both within and between each 100m repetition of the set. For 5 subjects, SL was consistently maintained as V increased (r = 0.02 ± 0.12), while the remaining subjects showed a significant decrease in SL (r = -0.61 ± 0.12; p < 0.05) during the latter half of the set . The results suggest that the interdependency of V & SR is related to propulsion, such that a greater hand/arm speed through the water and an increased number of strokes is related to an increased capacity to generate propulsive forces. The findings also demonstrate that SL is essentially fixed (presumably at its maximum level), until a point is reached at which it can no longer be maintained (a point likely related to anaerobic threshold). Future studies should attempt to describe the specific biomechanical and/or physiological relationships associated with V/SR dependency in competitive swimming.